Identification and functional analysis of growth- regulating factors involved in abiotic stress response in Chrysanthemum L. - Xu, Ye; Li, Jingjing; Liu, Kun; Zheng, Junping; Li, Kai; Wang, Huihui; Liu, Hongtao (Frontiers in Plant Science, 2026)
IntroductionChrysanthemum (Chrysanthemum L.) is highly valued for its ornamental appeal and medicinal properties. However, its growth is often adversely affected by various abiotic stresses. Growth-regulating factors (GRFs) are a class of plant-specific transcription factors, functioning critically in regulating development, growth processes, hormonal pathways, and environmental stress adaptation. However, the GRF gene family in Chrysanthemum species remains poorly characterized.MethodsGRF genes were systematically identified from four Chrysanthemum species (C. indicum, C. makinoi, C. nankingense, and C. lavandulifolium), followed by phylogenetic, evolutionary, and expression analyses. Subcellular localization and transcriptional activation assays were performed to characterize key GRF members.Results and DiscussionA total of 43 GRF genes were identified. Phylogenetic and evolutionary analyses revealed that these genes can be classified into four major clades, with their expansion primarily driven by whole-genome duplication and segmental duplication events. Expression profiling under various abiotic stress conditions - including NaCl, CdCl2, drought, high temperature, and low temperature - showed that many GRFs were significantly upregulated. Notably, CiGRF7 exhibited an expression increase of over 1000-fold under cold and CdCl2 stress, suggesting its key role in abiotic stress responses in Chrysanthemum. Subcellular localization confirmed the nuclear localization of the CiGRF7 protein. Additionally, transcriptional activation assays in yeast demonstrated that CiGRF7 possesses self-activating capabilities. Overall, this study provides a comprehensive overview of the GRF gene family in Chrysanthemum, shedding light on their evolutionary patterns and stress-responsive expression, and offers valuable genetic resources for future research on stress tolerance and growth regulation in this important ornamental and medicinal plant.